Arabic Language Learning In The Covid-19 Pandemic Period - Febria Syifa’unnnufus (INGGARA (Jurnal Pendidikan Bahasa Inggris dan Bahasa Arab), 2022)
The COVID-19 pandemic which is still ongoing today has a major impact on various sectors, one of which is education. The world of education also feels the impact. Educators must ensure that teaching and learning activities continue even though students remain at home. The solution is that educators are required to design learning media as innovations in learning by utilizing online media. The purpose of this study is as a form of general review of online learning during the covid-19 pandemic and what are the problems faced by teachers and students in the process of learning Arabic in the midst of the covid-19 pandemic. This research is included in the literature study. The analysis was carried out from various articles and similar sources related to online learning during the pandemic.